Economic feasibility of tomato (Solanum lycopersicum) production under protected and unprotected environment - SAGAR, ATISH; SINGH, P K (The Indian Journal of Agricultural Sciences, 2023)
Tomato (Solanum lycopersicum L.) is a high-value crop that is in high demand globally. The present study was carried out at G B Pant University of Agriculture and Technology (GBPUAT), Pantnagar, Uttarakhand during 2016–18 with the objective to explore the economic feasibility of tomato production under controlled and uncontrolled environments. The present study examines the costs and returns associated with the production of tomatoes in greenhouses and open fields, including the initial investment, operational costs, and revenue generated. The study found that greenhouse tomato production was more expensive, with a higher initial investment and operational costs, but generated higher yields and returns per unit area. On the other hand, open-field tomato production had lower initial investment and operational costs but had lower yields and returns per unit area. Overall, tomato production can be economically feasible under both controlled and uncontrolled environments, but the decision to use either method should be based on the specific conditions of each farm and the market demand for the product.